Manajemen kurikulum Sekolah Islam Terpadu - Nuralim Nuralim (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2022)
Curriculum is the core basis in learning, because the curriculum determines the direction of teaching-learning process in educational institution. A well-designed and executed curriculum will obtain a good quality education. This research aims to discuss in depth the management of an integrated curriculum, which includes four principles of management, those are: planning, organizing, implementation, and controlling (evaluation). The method used in this study is a qualitative descriptive method which collects data through interviews. The results showed that curriculum management at SMP Al Wildan Islamic School 3, BSD City applies four management principles, namely planning, organizing, implementing and controlling. The curriculum planning model used is a mixture of administrative and grassroots approach. The organization of curriculum carried out the integration between general science and Islamic value with a self-designed and internationally oriented. The program implementation is carried out the class level with a mobile class system and the control group carried out learning outcomes of students and educators.AbstrakKurikulum adalah inti dalam pembelajaran, karena kurikulum itu menentukan arah proses pendidikan suatu lembaga pendidikan. Kurikulum yang dirancang dan dijalankan dengan bagus akan menghasilkan kualitas pendidikan yang bagus juga. Penelitian ini bertujuan untuk membahas secara mendalam manajemen kurikulum sekolah Islam terpadu, yang mencakup empat prinsip manajemen, Planning (perencanaan), organizing (pengorganisasian), actuating (pelaksanaan) dan controlling (evaluasi). Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskripitif yang pengumpulan datanya dilakukan melalui wawancara. Hasil penelitian menunjukkan manajemen kurikulum di SMP Al Wildan Islamic School 3, BSD City menerapkan empat prinsip manajemen, yaitu planning, organizing, actuating dan controlling. Model planning kurikulum yang dilakukan adalah pencampuran antara administrative approach dan grass roots approach. Organizing kurikulum yang dilakukan adalah pemaduan antara ilmu umum dan ilmu agama Islam dengan desain yang dirancang secara mandiri dan berorientasi internasional, actuating program yang dilaksanakan pada tingkat kelas dengan system moving class dan controlling yang dilakukan mencakup hasil belajar murid dan kinerja tenaga pendidik.